DETERMINANTS OF VOLUNTARY DISCLOSURE: EMPIRICAL ANALYSIS OF PUBLIC LISTED ENTITIES IN INDONESIA - Supriyanto Supriyanto; Resnika Resnika (UNIB Press, 2023)
This experimental research explored the association between corporate governance mechanisms and the quality of voluntary corporate disclosure. Corporate governance structures encompass of the ownership structure, the effectiveness of the audit committee, and the quality of external auditors. The used technique of research is a quantitative methodology. The main emphasis of the study are the annual reports of public companies listed on the Indonesia Stock Exchange (IDX) between 2017 and 2021. In addition, the primary website of the stock market, www.idx.co.id, and issuer websites are reviewed for secondary data. The method of data analysis employed is panel regression analysis. 817 firms from all sectors of the Indonesia Stock Exchange make up the sample population generated by stratified sampling. The findings of this study indicate that the audit committee size and the age of the company incur impact on the voluntary disclosure of Indonesian issuers. On the other hand, it has been established that the structure of foreign ownership in Indonesia degrades the quality of voluntary disclosure. Also, research reveals that the audit quality of external auditors cannot consistently influence the company's information sharing. This report provides an overview of the quality of voluntary disclosures made by issuers in Indonesia. In addition, this study includes information on the drivers of voluntary disclosure that must be improved to increase stakeholders' competitiveness and trust.